2011
DOI: 10.1007/s11655-011-0815-y
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation-inhibiting and apoptosis-inducing effects of ursolic acid and oleanolic acid on multi-drug resistance cancer cells in vitro

Abstract: Both UA and OA have antitumor effects on cancer cells with MDR, and the optimal effect is shown by UA on colonic cancer cells. Also, UA shows cell apoptosis-inducing effect on SW480, possibly by way of down-regulating the expressions of apoptosis antagonistic proteins, Bcl-2, Bcl-xL, and survivin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 11 publications
3
40
0
Order By: Relevance
“…Moreover, we also detected decreased apoptotic tumor cells by the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay under hypoxia, which could be reversed by UA (data not shown). Additionally, inhibition of angiogenesis by UA was also confirmed by our current study and previous works (Shan et al, 2009;2011), which was also involved with HIF-1α accumulation. Therefore, UA could be a promising candidate to combine with current chemotherapy to reverse drug resistance and enhance tumor cell apoptosis under hypoxia.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, we also detected decreased apoptotic tumor cells by the terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay under hypoxia, which could be reversed by UA (data not shown). Additionally, inhibition of angiogenesis by UA was also confirmed by our current study and previous works (Shan et al, 2009;2011), which was also involved with HIF-1α accumulation. Therefore, UA could be a promising candidate to combine with current chemotherapy to reverse drug resistance and enhance tumor cell apoptosis under hypoxia.…”
Section: Discussionsupporting
confidence: 89%
“…(Apocynaceae), on MCF-7 and MDA-MB-231 cell lines and concluded that the anti-proliferative effect was due to the induction of apoptosis by extrinsic and intrinsic apoptosis pathways after exposure to the mixture. Shan et al (2011) reported UA and OA cytotoxic effects against MCF-7/wt cells and adriamycin resistant breast cancer cell line MCF-7/ADR with IC 50 of 30 and 40 lM UA, respectively. Our study on MCF-7 shows that after 72 h, even small concentrations such as 10 lM UA inhibited more than 90% of the breast cancer cells; similar results were obtained on MDA-MB-231 and T47D cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[38] Down-regulated NF-kB-regulated gene products cyclin D1, MMP-9, ICAM-1 VEGF, c-FLIP, survivin, Bcl-2, Bcl-xL [39] Induced apoptosis by modulating purinergic receptor P2Y(2)/Src/p38/Cox2 pathway [41] Reversed multidrug resistance in SW480 and SW620 [48] Ovarian carcinoma Suppressed cell proliferation, upregulated phosphorylation of ERK, and induced caspase 9 and 3 and effectively cleaved PARP [96] Down-regulated the expression of survivin, c-Myc and astrocyte elevated gene [96] Pancreatic carcinoma Inhibited proliferation of MIA-PaCa-2, PANC-1 and Capan-1 via PI3 K/AKT/NF-kB and JNK pathways [40] Induced cytotoxicity and induced p53, p21waf1, and NOXA in AsPC-1 cells [71] Chronic myelogenous leukemia cells and HL60 monocytes Induced apoptosis via down-regulation of Akt, up-regulation of PTEN and by activating mitochondrial pathway in K562 cells [42] Induced HL60 monocyte differentiation and up-regulated C/EBPb via ERK activation [43] Reversed multidrug resistance in K562/ADR and HL60/ADR [48] Lung carcinoma Induced apoptosis in A549, H3255 and Calu-6 in a dose and time dependent manner [51] Neuronal glioblastoma (astrocytoma) Inhibits proliferation and induces apoptosis in human glioblastoma cell lines U251 by suppressing TGF-beta1/miR-21/PDCD4 pathway [60] IRE1-TRAF2-ASK1 signaling complex to activate pro-apoptotic ASK1-JNK signaling. Salubrinal, an ER stress inhibitor, diminished ursolic acid-induced CHOP/Bim expression and anti-T24 cell effects [36].…”
Section: Biological Effects Referencesmentioning
confidence: 99%
“…Drug-resistance is one of the principal causes for chemotherapy failure in clinical practice, and a number of mediators including multi-drug resistance (MDR) proteins and the anti-apoptotic factors play an important role in this process [47]. Shan et al [48] recently highlighted the promising ability of ursolic acid to revert MDR in human colon cancer cell lines (SW480 SW620), human acute myelocytic leukemia cancer cell lines (HL60 and HL60/ADR), human chronic myelogenous leukemia cell lines (K562 and K562/ADR), human breast cancer cell lines (MCF-7 and MCF-7/ ADR), and also in doxorubicin-resistant HepG2 cells [49]. Lung cancer is one of the most common cancers that can affect cigarette smokers [50].…”
Section: Biological Effects Referencesmentioning
confidence: 99%